The potential introduction of police-issued family violence intervention orders in Victoria, Australia: Considering the unintended consequences. Issue 2 (3rd April 2022) - Reeves, Ellen
ABSTRACT: The Victorian Royal Commission into Family Violence, in its landmark 2016 report, recommended that in five years – 2021 – the Victorian Government consider expanding police powers to include the ability to grant on-the-spot family violence intervention orders. Such orders would see a bypassing of judicial oversight where deemed appropriate, thus mirroring the Tasmanian model, where police can issue orders for up to 12 months, unless the respondent seeks to have the order varied or revoked in court. There is currently a division in the family violence sector as to the appropriateness of police-issued civil protection orders, with many family violence advocates raising significant concerns. This article considers current debates regarding police-issued civil protection orders and highlights the misidentification of women victim-survivors of family violence as predominant aggressors as a possible unintended consequence of such reform. With the Victorian Government due to respond to Recommendation 59 of the Royal Commission into Family Violence this year, this commentary provides a timely analysis of sector debates and reinforces the potential harms of increasing police powers in a space where they have historically responded poorly.